Analisis Kinerja Perangkat Desa dalam Penyelenggaraan Pemerintahan Desa: Studi Deskriptif di Desa Laut Dendang - Fahreza Rizki Tabrani; Farhan Azra Hasibuan; Meliana Girsang; Julia Ivanna (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2023)
This study aims to analyze the performance of village officials in administering village administration in Laut Dendang Percut Sei Tuan Village. The research used is a type of qualitative research, the form of this research is descriptive qualitative. Data collection techniques by means of interviews, observation, documentation and literature studies. The results of the study show that the performance of village officials in administering village administration in Laut Dendang Percut Sei Tuan Village is quite good where productivity performance, service quality, responsiveness, responsibility and accountability of village officials in organizing village governance are good. However, the performance of the Laut Dendang village apparatus also has weaknesses so that it does not go completely well. There are several problems that affect the performance of village officials such as lack of human resources, lack of support from the government and lack of public awareness in providing participation in the performance of village officials.